Preschoolers' Empathy Profiles and Their Social Adjustment - Simon, Poline; Nader-Grosbois, Nathalie (Frontiers in Psychology, 2021)
Preschoolers face new challenges in their social life: the development of social and emotional abilities in order to have positive relationships with peers and adults. Empathy, the ability to share and understand the emotions of others, contributes to this socio-emotional adjustment. This exploratory study examines mothers and fathers’ perceptions of their child’s empathy and individual factors, such as age, gender and personality, which are related to cognitive and affective empathy in 63 typically developing preschoolers. Links between children’s individual characteristics (empathy and personality -) and their social adjustment on the one hand and risk of developing internalized vs. externalized behaviors on the other were also investigated. Parents completed four questionnaires about their child’s empathy, personality, and social (mal)adjustment. The results showed that mothers and fathers perceived their children’s cognitive and affective empathy, attention to others’ feelings and social actions (such as helping), in the same way, except for emotion contagion. Gender differences appeared specifically for some components of empathy: girls were said to pay more attention to others’ emotions while boys had better cognitive empathy. Moreover, children’s empathy as perceived by mothers or fathers was positively linked with their age, and with personality factors (extraversion, emotional stability, agreeableness and openness to experience). Cognitive empathy and personality were found to be partly related to higher social skills and lower externalized and internalized behaviors. The results nuanced specific links between cognitive and affective empathy and social adjustment as well as behavior problems at preschool age. These results may have some implications for future research and prevention in childhood.